(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Human immunodeficiency virus (HIV) is a virus that attacks the body’s immune system. Acquired immunodeficiency syndrome (AIDS) occurs at the most advanced stage of infection. HIV targets the body’s white blood cells, weakening the immune system. This makes it easier to get sick with diseases like tuberculosis, infections and some cancers. HIV is spread from the body fluids of an infected person, including blood, breast milk, semen and vaginal fluids. It is not spread by kisses, hugs or sharing food. It can also spread from a mother to her baby.